Technology Bill of Rights Needed to Protect Human and Environmental Health and the U. S. Constitutional Republic - Herndon, J. Marvin; Whiteside, Mark (Advances in Social Sciences Research Journal, 2020)
For the protection of humanity and the planetary environment in general, and American citizens in particular, what is needed, we posit, is a set of new Constitutional Amendments that collectively form a second Bill of Rights, a Technology Bill of Rights, to protect our freedoms, health, air, water, agriculture, and the planetary environment from deliberate perversion and alteration. We describe the rationale for said Technology Bill of Rights that would: (1) Prohibit the application of any technique or method for changing – through the deliberate manipulation of natural processes – the dynamics, composition or structure of the Earth, including its biota, lithosphere, hydrosphere and atmosphere, or of outer space; (2) Prohibit the application of any technique, including software-based process or platform or method for violating individuals free speech, censoring, altering, editing, deleting, excluding, blacklisting, or engaging in any activities that potentially bias votes or deceive the public on matters of health and/or environmental harm; and, (3) Prohibit activities of such scale and nature that would intentionally or unintentionally alter the complex but delicate balance in nature by and between myriad biota and their environments that makes our planet habitable for life. Whereas the meaning of (1) and (2) above is clear, (3) necessitates further clarification that may be inferred from the following non-exclusive examples of prohibited activities: ● Use of metallic and/or nano-particulate additions to aircraft fuel; ● Excessive launching of satellites, numbering in the tens of thousands, whose rocket exhaust might damage the ozone layer; ● Excessive exposure of humans and other biota to electromagnetic radiation; ● Use of electromagnetic radiation to heat the ionosphere; ● Pollution of air, land, water, agriculture, and aquaculture by particulates, toxic chemicals, heavy metals, radioactive nuclides, and bio-toxins; and, ● Strict oversight of biotechnology/bioengineering, including prohibition of gain-of-function experiments with potential pandemic pathogens.